Tariffs, The Terms of Trade and Domestic Prices in a Monetary Economy - Batra, Raveendra N.; Ramachandran, Rama (Review of Economic Studies, 1980)
Raveendra N. Batra, Rama Ramachandran; Tariffs, The Terms of Trade and Domestic Prices in a Monetary Economy, The Review of Economic Studies, Volume 47, Is